The Influence of Market Orientation with Product Innovation of Hydroponic Vegetables in Bogor City, West Java - Miftah, Himmatul; Limakrisna, Nandan; Hanan, Sufrin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Vegetables are one of the leading agribusiness commodities because, in addition to having a relatively high economic value, the trend of demand is increasing. This study aims to identify the market orientation of hydroponic vegetable producers, determine the effect of market orientation on the marketing innovation of hydroponic vegetable companies, and determine the impact of market orientation on vegetable marketing performance mediated by innovation. Respondents in this study totaled 60 people. The results concluded that market orientation has a significant effect on innovation. This research concludes that market orientation is critical to pay attention to because it will influence the company to innovate.